QUALITY ANALYSIS OF BASIC RESOURCES FROM THE ASPECT OF FEASIBLITY OF ALUMINA CEMENT PRODUCTION - M. Perušić; D. Lazić; Z. Obrenović; G. Ostojić (Journal of Engineering & Processing Management, 2009)
Main objective of this paper is feasibility of alumina cement production on the Republic of Srpska resources basis. As is known calcium-alumina cement is type of mineral hydraulic binder. As basic resources of CAC production are used bauxite and calcite. There are two main production processes: the fusion, Al2O3 less than 50% and the sintering process, Al2O3 higher than 50%. Republic of Srpska has two main bauxite deposits: Milici and Srebrenice mines and alumina factory in Zvornik. There are a couple calcite deposits with possible CAC technology requirements. Also the nearest CAC factory is in Istria, Republic of Croatia.
Keywords: bauxite; cement; calcite